Quantifying Quantum Correlation of Quasi‐Werner State and Probing Its Suitability for Quantum Teleportation. Issue 10 (5th July 2021) - Chatterjee, Arpita; Thapliyal, Kishore; Pathak, Anirban
Abstract: The significance of photon addition in engineering the single‐ and two‐mode (bipartite correlations) nonclassical properties of a quantum state is investigated. Specifically, the behavior of the Wigner function of two quasi‐Werner states constructed by superposing two normalized bipartite m ‐photon added coherent states are analyzed. This allows the authors' to quantify the nonclassicality present in the quantum states using Wigner logarithmic negativity (WLN), while quantum correlations are measured using concurrence, entanglement of formation, and quantum discord. The WLN for a two‐mode state corresponds to the sum of the single‐mode nonclassicality and quantum correlations, and both of these are observed to enhance with photon addition manifesting the efficacy of photon addition in the entanglement distillation. Usefulness of photon addition is further established by showing that the performance of the quasi‐Werner states as quantum channel for the teleportation of single‐mode coherent and squeezed states, as quantified via teleportation fidelity, improves with the photon addition. The non‐Gaussian operation is shown effective in stalling the detrimental effects of transmission through noisy channel and/or inefficient detection under realistic scenario. Further, in contrast to a set of existing results, it is established that the negative values of two‐mode Wigner function is not a witness of quantum correlation. Abstract : The advantage of photon addition in engineering the single‐mode nonclassicality and bipartite correlations is quantified using Wigner logarithmic negativity, concurrence, and quantum discord. Further, teleportation of coherent and squeezed states using this state as a quantum channel establishes the non‐Gaussian operation as an effective tool to combat the detrimental effects of noise and inefficient detection under the realistic scenario.